Impact of Intermittent Fasting on Glycemic Control in Obese Patients with Type 2 Diabetes - Mohammed Ahmed Alqahtani; Mohammad S. Alshahrani; Abdullah Mohammed Saeed Al-Shalaan; Abdullah Mohammed Hassan Alshamrani; Osamah Abdulaziz Ali Al salmh; Ayedh Mubarak Ayedh Aljunaybi (International Journal of Medical Toxicology and Legal Medicine, 2025)
Intermittent fasting (IF) has gained considerable traction as a dietary strategy not only for weight management but also for improving metabolic health, particularly among those at risk for or diagnosed with type 2 diabetes (T2D). Among the various fasting protocols, researchers have explored the effects of IF on glycemic control, with particular emphasis on its influence in obese patients who often experience significant metabolic disturbances. This paper reviews and synthesizes the current literature surrounding intermittent fasting's role in enhancing glycemic control, insulin sensitivity, and metabolic markers in obese individuals diagnosed with T2D. By evaluating findings from various clinical trials and observational studies, this review delineates the potential advantages of IF, underlying mechanisms, as well as limitations and challenges associated with its application. Moreover, the potential for integrating IF into dietary recommendations for managing T2D is considered, aiming to provide data-driven insights for clinicians and healthcare professionals.